Measurements of ϒ states production in 𝑝 + 𝑝 collisions at √𝑠 = 500 GeV with STAR: cross sections, ratios, and multiplicity dependence - Aboona, Bassam; Deppner, Ingo Martin; Herrmann, Norbert; Leung, Yue; Söhngen, Yannick (Physical review, 2025)
We report measurements of ϒ⁡(1⁢𝑆), ϒ⁡(2⁢𝑆) and ϒ⁡(3⁢𝑆) production in 𝑝 +𝑝 collisions at √𝑠 =500 GeV by the STAR experiment in year 2011, corresponding to an integrated luminosity ℒint =13 pb−1. The results provide precise cross sections, transverse momentum (𝑝T) and rapidity (𝑦) spectra, as well as cross section ratios for 𝑝T <10 GeV/c and |𝑦| <1. The dependence of the ϒ yield on charged particle multiplicity has also been measured, offering new insights into the mechanisms of quarkonium production. The data are compared to various theoretical models: the color evaporation model (CEM) accurately describes the ϒ⁡(1⁢𝑆) production, while the color glass condensate+nonrelativistic quantum chromodynamics (CGC+NRQCD) model overestimates the data, particularly at low 𝑝T. Conversely, the color singlet model (CSM) underestimates the rapidity dependence. These discrepancies highlight the need for further development in understanding the production dynamics of heavy quarkonia in high-energy hadronic collisions. The trend in the multiplicity dependence is consistent with CGC/saturation and string percolation models or ϒ production happening in multiple parton interactions modeled by pythia8.
Veröffentlicht: 15. August 2025
Gesehen am 30.01.2026